RECORD KEEPING AND DATA MANAGEMENT WITHIN THE POLICY DESIGN OF ADULT EDUCATION PROGRAMMES IN NIGERIA - Muhammad, Alkali (Sokoto Educational Review, 2020)
One of the identified setbacks in the realization of the set objectives of the adult education programme in Nigeria is the poor or near absence of adequate records keeping and data management. In the organization of the programme very little attention is paid to record keeping and data management, officials lack the required knowledge, adequate financial provision is not made for the department, thus resulting in general apathy and lack the required information and data that will have gone a long way in the effective planning of the programme for the required results. In this paper an attempt will be made to highlight the importance of record keeping and data management, the types of records and methods of keeping and management that will yield optimum results.